Improving cycling environment in a Green Park based on the post-occupancy evaluation method. Issue 2 (4th March 2023) - Xu, Congbao; Ma, Qingsong; Lu, Yunqin; Liang, Qingqing; Gao, Weijun
ABSTRACT: Nowadays, urban cycling activities in China are developing rapidly, and the number of cyclists has also increased dramatically. The improvement of urban cycling environment design in cities has positive significance for improving the quality of living environment. However, the related research about the environmental design theory is relatively scarce in China. This paper tries to apply the Post-Occupancy Evaluation (POE) method to evaluate the cycling environment in a green park. This study investigates the problems of the cycling environment of a park in Qingdao and then proposes some methods for improvement. The evaluation model is established by using the analytic hierarchy process (AHP) to assess the cycling environment. POE has been carried out by collecting data through questionnaires. The low score of POE has shown the shortcomings of the green park cycling design. Furthermore, this study proposes some principles of systematization, people-oriented, refinement and ecological economy to optimize the cycling environment of the green park. This paper creates a new method of designing the cycling environment, namely "POE – behavior analysis – design optimization", which provides a theoretical reference for cycling environment design of the green park. GRAPHICAL ABSTRACT: uf0001